F. Iskander’s Story “Belshazzar’s Feasts” in the Context of Intertextual Сonnections - MKRTCHYAN, MARIANNA (Bulletin of Yerevan University H: Russian Philology, 2021)
The purpose of this paper is to examine the intertextual connections between F.Iskander’s story “Belshazzar’s Feasts” and the Book of Daniel. The content of the story is analysed in the context of the carnival tradition too. On the one hand, Stalin’s character as a tyrant is compared with Nebuchadnezzar, king of Babylon. On the other hand, Stalin’s figure is examined as the temporary king of carnival, whose part could be performed by a criminal condemned to death and whose execution is predetermined by the ritual. In Iskander’s story Stalin’s death is a sign of punishment for the crimes committed by him. The author’s description of Stalin’s banquet demonstrates the aberration of the folk carnival tradition, at the same time keeping the essential ambivalence of the carnival unchanged.